Pengaruh Adversity Quotient Terhadap Kemampuan Pemecahan Masalah Matematis Siswa : Systematic Literatur Review - Shela Apriliana; Putri Nur Malasari (JUMAT: Jurnal Matematika, 2023)
There have been many studies conducted on the influence of students' AQ levels in learning, especially learning mathematics. Therefore, research that summarizes the research findings of AQ in mathematics teaching is needed. Adversity Quotient can be understood as a person's skill in using his intelligence to be able to survive, face difficulties, reduce difficulties and obstacles into opportunities by improving the way of thinking and acting. The purpose of this study is to show that the AQ level of each student has an effect on their ability to solve and solve math problems. This study uses a method in the form of Systematic Literature Review (SLR) in doing research. Study stage Systematic Literature Review (SLR) is planning, conducting, and reporting. The synthesis of studies related to the purpose of this study was carried out using Google Scholar which obtained 10 primary studies published from 2018-2023. The results of the study provide information that the level of fighting power affects students' ability to solve mathematical problems. Type student quitter in solving problems only able to understand the problem. In problem solving, students type camper able to complete the three stages of Polya. Meanwhile, AQ students climber able to complete the four stages of Polya in solving problems. Therefore, because students' problem-solving abilities vary, teachers must be careful in seeing and estimating the extent of students' AQ levels in learning mathematics.